Strategic Management Accounting disclosure, ownership structure, and firm characteristics in Indonesia manufacturing companies - Honggowati, Setianingtyas; Rahmawati, Rahmawati; Aryani, Y Anni; Probohudono, Agung Nur (Jurnal Keuangan dan Perbankan, 2019)
Why managers should choose to disclose their information with investors is one of the major issues in accounting research. Because of information asymmetry and the agency problem, disclosure is an important aspect of the modern capital market. This study aims to measure the extent of Strategic Management Accounting (SMA) disclosure and the impact of ownership structure (managerial ownership, foreign ownership, government ownership) and firm characteristics (firm size, leverage, profitability) on SMA practices in annual reports of Indonesia manufacturing companies. Â The annual reports of 545 listed companies for 2012â€“2016 were examined to measure the extent of SMA disclosure and investigate potential determinant factors of SMA disclosure. This study used 42 items of weighted disclosure index, based on international guideline and SMA literature. This study used multiple regression analysis to examine the association between ownership structure, firm characteristics, and SMA disclosure. The results indicate a low extent of SMA disclosure in annual reports of Indonesia manufacturing companies. The average of SMA disclosure rate is only 39.4 percent, which indicates that SMA has not been commonly disclosed in annual reports. Further results indicate that only leverage that has an insignificant effect on the extent of SMA disclosure. The finding regarding SMA disclosure in annual reports should be on concern to regulatory authorities and standard-setters in Indonesia.JEL Classification: G30, G32, G34DOI: https://doi.org/10.26905/jkdp.v23i3.3228Â